Green consumer behaviour on green products among Generation Y in Malaysia and Nigeria : a cross-cultural comparative study - Ogiemwonyi, Osarodion (2021)
In recent decades, due to environmental hazards, green purchasing has been subject to a wide range of research. Subsequently, the understanding of the theoretical structure of green consumer purchasing behaviour is becoming increasingly important for both academics and policymakers. Therefore, this study aims to understand the differences in green consumer behaviour among Generation Y Cohort (the age range among 18-32 years) individuals with higher education linked with sizeable income. Based on the literature review, eight research questions have been formulated. A quantitative approach is designed and a survey has been carried out using a questionnaire-based approach to capture the consumer groups from Kuala-Lumpur, Malaysia (n= 280) and Abuja, Nigeria (n=267). The study utilized the Theory of Planned Behaviour (TPB) model and the Green Contextual Factor (GCF) are used to build the constructs to examine Generation Y green behaviour. Partial Least Squares Path Modelling (PLS-PM) and Multigroup Analysis (MGA) are used to estimate the results on SmartPLS. The role of attitude as a mediator in the relationship between (GCF) and green behaviour has been examined. The findings show that (MGA) confirmed the existence of significant differences in the study. To solicit responses that could not has been anticipated from both samples, the study applied an open-ended format in addition to the closed-ended questions to further compare the responses. In both sets, 40 per cent purchase green products because of environmental benefits in Malaysia, while 54 per cent purchase green products because of health benefits in Nigeria. The path coefficient results indicate that perceived behavioural control has a significant impact on green behaviour among Generation Y in Nigeria, but not among Malaysia samples. In both Malaysia and Nigeria, green product trust and value have significant impact. Although, trust is stronger among Malaysia samples, while value is stronger in Nigeria. Awareness and price sensitivity are not significant in both samples. Green culture and Attitude significant impact on green behaviour for both Generation Y in Malaysia and Nigeria and is stronger in Nigeria. Attitude mediates between perceived behavioural control, price sensitivity, green culture, and behaviour in both Malaysia and Nigeria samples. However, in both samples, attitude shows no mediation on trust, value, and awareness. The findings indicate that at the time of the study, environmental activism in Malaysia and Nigeria are not motivated nor the people (Generation Y) understand how some specific behaviour is harmful to the environment. Based on the result, it is not sufficient to only provide citizens with relevant facts, but the objective of the facts should also be revealed ethically and impartially. Findings from the study could be used to develop policies and convincing communication strategies to promote green behaviour for Malaysia and Nigeria’s public and private sector. Thus, the study contributes to developing green consumer profile among Generation Y in Malaysia and Nigeria by identifying consumer patterns for a peaceful future.